Exploration of Black Swan Dumpling, A High-Quality Culinary - Giri, Julio Marvel; Widyanata, I Putu Aditya; Wijaya, I Putu Ari; Agastya, I Putu Arya; Putra Pradyasta, I Putu Arya Dharma; Arya Pratama, I Putu Dharma; Santi Diwyarthi, Ni Desak Made (Jurnal Multidisiplin West Science, 2024)
This study is a descriptive research with a phenomenological approach, conducting qualitative research methods about black swan dumpling. Qualitative research methods aim to understand phenomena deeply from the subjects' perspective. Common methods include depth interviews, participant observation, and literature review. Depth interviews involve in-depth discussions with respondents to understand their views comprehensively. Participant observation entails direct involvement in a situation to grasp its dynamics. Literature review analyzes relevant sources to understand existing knowledge of black swan dumpling, as well as the barriers and opportunities for its development. The results reveal that black swan dumpling has the authenticity and uniqueness from its specific ingredients, preparation techniques, cultural significance, and adaptability to global markets. The dumplings require specific skills and traditions, using quality ingredients like swan meat. The cultural significance, makes dumpling as symbolic of celebrations and gatherings. The diverse fillings, cooking methods, and fusion possibilities, make black swan dumplings versatile and appealing in a global culinary landscape.